HACCP in action [ food safety case studies - Leigh, Richard , 1943-2007; Lovitt, Zane; McAuliffe, Mark (VEA, 2005)
The HACCP system - Hazard Analysis Critical Control Points was developed in the 1960s in the US and was used in the NASA space program. This program analyses and explains this scientific system, which identifies specific hazards and measures for their control, ensuring food safety. HACCP can be applied throughout the food chain from primary production through to consumption and also aids in the inspection of food premises by regulatory authorities, ensuring confidence in export industries that the food we produce is safe